Analysis of fetal surgery as a treatment for myelomeningocele: fetoscopy repair versus open repair a systematic review (Research, Society and Development, 2022)
Introduction: Myelomeningocele (MMC) is the most severe form of spina bifida characterized by the protrusion of the spinal cord and meninges through a spinal defect and a spectrum of clinical manifestations, including hindbrain hernia, hydrocephalus, sensory and motor neurological deficits. , bowel dysfunction, and urinary dysfunction. Objectives: to analyze fetal surgery as a treatment for myelomeningocele (MMC), comparing the fetoscopy repair and the open repair. Method: a computerized literature search was performed, using the descriptors: meningomyelocele, spina bifida, spinal dysraphism, repair, closure, pre -natal care, prenatal care, fetal and in utero surgery, in the following databases (SciELO, Revista Brasileira de Neurocirurgia and PubMed). Results: We analyzed 11 studies and found no difference in mortality or in the rate of shunt placement for hydrocephalus. Percutaneous fetoscopic repair was associated with higher rates of premature rupture of membranes and preterm delivery (96 vs. 81%) compared with open repair, while fetoscopic repair by maternal laparotomy reduced preterm birth. Discussion: Fetoscopic repair is a promising alternative for open repair of fetal MMC with a lower risk of uterine dehiscence; however, fetoscopic techniques must be optimized to overcome the high rate of dehiscence and leakage at the   MMC repair site. Conclusion: Based on the results of our meta-analysis, the main limitations of fetoscopic MMC repair are premature rupture of membranes (PROM) and a high rate of dehiscence or leakage at the   MMC repair site that requires postnatal review.